การทำกิจกรรมเพื่อส่งเสริมความผูกพันระหว่างมารดา-ทารกโดยเร็ว และการให้นมแม่ครั้งแรกในห้องคลอด โรงพยาบาลรามาธิบดี - yoorat, yingkwan; punyavachira, Piyaporn (Nursing Research and Innovation Journal, 2015)
This retrospective study aimed to examine rate, duration of promoting early bonding and baby breast crawl behavior and the outcome of early initial breastfeeding stimulation. The samples consisted of 1,475 mothers and their newborns who were delivered by spontaneous vaginal delivery in the labour room, Ramathibodi Hospital during January-December 2011. Data were collected from the breastfeeding record in labour room and the client’s medical records. Data were analyzed by using descriptive statistics. The results showed that 49.4 percent of the samples were promoted. Only 2.33 percent were promoted for 20 minutes or longer and 0.96 percent of the babies had baby breast crawl. 93.14 percent of the promoted had successfully begun initial breastfeeding. This study shows lower rate and duration of promoting early bonding and baby breast crawl behavior than 50 percent. The findings from this study can be used as basic information for further investigation of causes and factors which are barriers to early bonding promotion before proper intervention will be developed. Keyword: early bonding promoting intervention, initial breastfeeding stimulation *This research was supported by a research fund, Faculty of Medicine Ramathibodi Hospital, Mahidol University. **Professional Nurse, Faculty of Medicine Ramathibodi Hospital, Mahidol University. ***Head Nurse, Labour Room, Department of Nursing, Faculty of Medicine Ramathibodi Hospital, Mahidol University.